2014
DOI: 10.1016/j.ultras.2013.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Multi-frequency axial transmission bone ultrasonometer

Abstract: The last decade has seen a surge in the development of axial transmission QUS (Quantitative UltraSound) technologies for the assessment of long bones using various modes of acoustic waves. The condition of cortical bones and the development of osteoporosis are determined by numerous mechanical, micro-structural, and geometrical or macro-structural bone properties like hardness, porosity and cortical thickness. Such complex manifestations of osteoporosis require the evaluation of multiple parameters with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Most measurement methods using QUS techniques to assess bone quality consider either transverse (Mathieu et al 2013) or axial (Tatarinov et al 2014) transmission configurations. The use of one single transducer in echographic configurations remains difficult due to accuracy and reproducibility issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most measurement methods using QUS techniques to assess bone quality consider either transverse (Mathieu et al 2013) or axial (Tatarinov et al 2014) transmission configurations. The use of one single transducer in echographic configurations remains difficult due to accuracy and reproducibility issues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as ultrasound is composed of mechanical waves, it can be used to retrieve useful information on bone biomechanical properties and therefore provide information additional to that provided by bone mineral density (BMD) estimation alone (Ha€ ıat et al 2008a). QUS is now widely used in the clinic in the context of osteoporosis to estimate bone quality at such sites as the calcaneum (Chin and Ima-Nirwana 2013), phalanx (Olszynski et al 2013), tibia (Maatta et al 2014), femur (Barkmann et al 2008) and radius (Sasso et al 2009) using transverse (Mathieu et al 2013) and axial (Tatarinov et al 2014) transmission devices. Speed of sound (SOS) is a QUS parameter (Haiat et al 2005b) that has been found to be related to bone strength (Haiat et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Guided mode propagation in cortical bone is investigated using the so-called axial transmission technique in which the signal propagating along the bone axis is recorded at multiple positions aligned along a same side of a skeletal site, by moving a receiver, [5][6][7][8] or moving both the transmitter and the receiver in parallel, 9 or using a multiple element array, [10][11][12] , or using photo-acoustic excitation and optical detection. 13 The first version of the axial transmission approach consisted in recording the time-of-flight of the earliest component of the signal recorded at the receivers, the so-called first arriving signal (FAS).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed description of the device has been previously reported [20]. Examination is conducted with the subject in the sitting or lying position.…”
Section: Methodsmentioning
confidence: 99%
“…The technology implemented in the initial design of BUSS has been significantly improved and modified enabling the device to radiate and receive a train of multiple impulses that generate various modes of acoustic waves. The details of the multi-frequency approach and a new version of the broadband BUSS device are described in our companion paper in this issue of Ultrasonics [20]. In this article, the results of a multi-parametric analysis of axial profiles in broadband frequency range obtained by BUSS in a multisite clinical study are presented and clinical significance of these results is discussed.…”
Section: Introductionmentioning
confidence: 99%